The Influence of The Paternity Class on Father’s Knowledge and Support for The Essential Newborn Care - Sri Sukamti; Wahyudin Rajab; Willa Follona; Hariyanti (Women, Midwives and Midwifery, 2022)
Background: The period after birth is the beginning of a baby's life. However, it is difficult for babies to adapt themselves to the extrauterine life that is extremely different with the intrauterine environment. This adjustment process is complicated, so babies need optimal care. Mothers are not always abl Background: The period after birth is the beginning of a baby's life. However, it is difficult for babies to adapt themselves to the extrauterine life that is extremely different with the intrauterine environment. This adjustment process is complicated, so babies need optimal care. Mothers are not always able to take care of their babies alone. Therefore, fathers’ participation is required to provide optimal care for babies. Purpose: This study aims to establish a forum for fathers-to-be to support the essential newborn care at home through a paternity class. Methods: This study used the quasi-experiment design without a control group. It involved father or father-to-be respondents with at least 30 samples. Respondents were selected based on the inclusion and exclusion criteria. The data was analyzed using a different mean test to determine the influence of the paternity class on father’s knowledge and support for the essential newborn care at home. Results: The results of this study showed that the paternity class had no influence on father’s knowledge, but it affected father’s support for the essential newborn care with p-value of 0.036. Conclusion: The paternity class influenced father’s support for the essential newborn care. The paternity class is one of the efforts to improve insight and father’s support for the care of young babies. This paternity class can be done periodically and continuously to help increase father’s support for infant-toddler and pre-school children care. e to take care of their babies alone. Therefore fathers participation is required to provide optimal care for babies. Purpose: This study aims to establish a forum for fathers-to-be to support the newborn care at home through a paternity class. Methods: This study used the quasi-experiment design without a control group. It involved father or father-to-be respondents with at least 30 samples. Respondents were selected based on the inclusion and exclusion criteria. The data was analyzed using a different mean test to determine the influence of the paternity class on father’s knowledge and support for the primary newborn care at home. Results: The results of this study showed that the paternity class had no influence on father’s knowledge, but it affected father’s support for the primary newborn care with p-value of 0.036. Conclusion: the paternity class influenced father’s support for the primary newborn care. The paternity class is one of the efforts to improve insight and father’s support for the care of young babies. This paternity class can be done periodically and continuously to help increase father’s support for infant-toddler and pre-school children care. Keywords: paternity class; knowledge; family support